Marital happiness of married visually disabled persons: Anintrinsic case study - Teoh Jia Long; Muhammad Idris Bullare @ Bahari (2018)
This paper aims to explore the sources of marital happiness among married visually disabled persons. Thedriving force of this study is the lack of theoretical and scholarly insights regarding the happiness ofvisually disabled spouses especially in Malaysia. This study will apply the qualitative methodology whichutilizes the case study design (Stake, 1995). One respondent was interviewed in this investigation. Eightthemes that best represent marital happiness of visually disabled person were constructed: responsibility,acceptance, self-efficacy, achievements, access to transportation, spirituality, sense of togetherness, andfinancial stability. Through this research, proper understanding of marital happiness among marriedvisually disabled persons could be obtained hence, serving as the guideline of policy making to ensurewell-being in such population. In this sense, the study of marital happiness among such population is alsocrucial to expand the plethora of knowledge in the field of positive psychology